2014
DOI: 10.1111/ors.12129
|View full text |Cite
|
Sign up to set email alerts
|

The role of the dental practitioner in diagnosing connective tissue and other systemic disorders: a case report of a patient diagnosed with type III Ehlers–Danlos syndrome

Abstract: An adolescent patient was referred to our specialist oral surgery unit for orthodontic exposure of an ectopic upper canine. The medical history revealed a recent diagnosis of mitral valve prolapse as well as an anecdotal tendency towards regular fainting/lethargy. Examination revealed a hypermobile temporomandibular joint, and an orthopantomogram showed lower supernumerary premolar teeth. Combined, these findings indicated a likely underlying connective tissue disorder, and an indirect referral to a specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
3
7
1
Order By: Relevance
“…In the present study, a genetic test was performed to improve the homogeneity of the sample and thereby the diagnostic significance of the results. Furthermore, the 26 hEDS patients compose a comparatively large number of subjects in accordance with previous reports, where oro‐dental manifestations of EDS have mostly been based on case reports and case studies and in some cases with undefined EDS subtypes. A previous clinical study, which included various EDS subtypes, did not perform a molecular confirmation of the participating EDS patients, and the number of individuals in each EDS subtype group was relatively small.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In the present study, a genetic test was performed to improve the homogeneity of the sample and thereby the diagnostic significance of the results. Furthermore, the 26 hEDS patients compose a comparatively large number of subjects in accordance with previous reports, where oro‐dental manifestations of EDS have mostly been based on case reports and case studies and in some cases with undefined EDS subtypes. A previous clinical study, which included various EDS subtypes, did not perform a molecular confirmation of the participating EDS patients, and the number of individuals in each EDS subtype group was relatively small.…”
Section: Discussionsupporting
confidence: 86%
“…It is advantageous for the dentist to know about specific oro‐dental characteristics in EDS in order to detect an undiagnosed or a mildly affected EDS patient and thereby improve diagnosis and allow a better‐targeted treatment. Previously, only few studies have investigated oro‐dental characteristics clinically and radiologically in hEDS patients, and to our knowledge, measurements of the crowns, roots, and bone level on CBCTs in hEDS patients compared to controls have not previously been described. In the present study, a genetic test was performed to improve the homogeneity of the sample and thereby the diagnostic significance of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both methods produced significant results but demonstrated that the methodology could widely change the prevalence of and therefore usefulness of such a sign. It has also been noted that up to 50% of EDS patients are able to touch their tongue to their nose (Gorlin sign) but it is unclear if the absence of the lingual frenulum has an impact on the presence of this sign [Tanwar et al, ; Awal et al, ].…”
Section: Oral Soft Tissue Manifestationsmentioning
confidence: 99%